(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
Some questions underlying the “UNIJES Declaration about the Democratic Regeneration of Public Life in Spain” are exposed. The Declaration itself can be read in full in the Annex to the article. Questions discussed include: the connection between Ethics and Politics, the popular relationship with the national State as an instrument of policy, the priority of politics over the economy, patrimonialism in the Spanish public life, and to whom the UNIJES Declaration is addressed.